Laboratory Evaluation of Plant Extracts as Antifeedant Against the Lesser Mealworm, Alphitobius diaperinus and Rice Weevil, Sitophilus oryzae - Kamruzzaman, M.; Shahjahan, M.; Mollaha, M. L. R. (Biological Sciences - PJSIR, 2005)
Studies were conducted on leaf, seed and bark extracts (acetone, ethanol and water) of Ipomoea fistulosa,Datura fastuosa,Eucalyptus citridora,Helitropium indicum,Hedyotis corymbosa and Sapium indicum for their antifeedant effects against the lesser mealworm, Alphitobius diaperinus and rice weevil, Sitophilus oryzae. The results showed that all the extracts of test plants had antifeedant effect on both the insects. Among the six plant extracts tested, Sapium indicum extracts had the highest antifeedant effect on the lesser mealworm and rice weevil. The ethanol extracts of leaf and seed were more effective than those obtained in the other two solvents. The coefficient of deterrency increased proportionally with increase in doses. The seed extract was more effective than leaf extract.